2018
DOI: 10.1093/jhps/hny006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and morphological features of acetabular dysplasia with coexisting femoroacetabular impingement-related findings in a Japanese population: a computed tomography-based cross-sectional study

Abstract: The coexistence of acetabular dysplasia (AD) and femoroacetabular impingement (FAI) has not been well discussed. This study was performed to elucidate the prevalence and morphological features of AD with coexisting FAI-related findings in a Japanese population. Computed tomography images were retrospectively evaluated. AD was classified as definite or borderline. The morphological findings that defined cam deformity were an α angle of ≥55°, head–neck offset ratio (HNOR) of <0.13, pistol grip deformity positivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The presence of concomitant hip dysplasia and femoroacetabular impingement (FAI) is relatively common. 40 Patients with BHD and cam-type FAI are more likely to demonstrate cam impingement in the proximal rather than distal region of the femoral neck. 27 Anderson et al 2 retrospectively reviewed 164 patients with symptomatic acetabular dysplasia who underwent a PAO.…”
Section: Bony Anatomymentioning
confidence: 96%
“…The presence of concomitant hip dysplasia and femoroacetabular impingement (FAI) is relatively common. 40 Patients with BHD and cam-type FAI are more likely to demonstrate cam impingement in the proximal rather than distal region of the femoral neck. 27 Anderson et al 2 retrospectively reviewed 164 patients with symptomatic acetabular dysplasia who underwent a PAO.…”
Section: Bony Anatomymentioning
confidence: 96%
“…Previous reports have described the presence of a “herniation pit” on computed tomography or magnetic resonance imaging as a feature of FAI patients. 9,19,20 This pit or lesion forms under compressive forces. This phenomenon is very similar to what occurs to the subchondral area of tibia in knee osteoarthritis, which is affected by the compression between the distal femur and the proximal tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Although some researchers consider labral lesions in AD to be related to instability of hip joint, others have emphasized that there are AD patients who have symptoms of impingement similar to FAI patients. 9…”
Section: Introductionmentioning
confidence: 99%
“…The cohort of asymptomatic men ( n = 244) elucidated that the cam-type deformity was related to the herniation pit, labrum tear, and decrease in the cartilage thickness [14]. A cross-sectional Japanese population study revealed that the rate of coexistence of acetabular dysplasia was 23.4% in patients with FAI [9]. On the contrary, owing to the mechanical stress to the labrum, the dysplastic hip is at risk for abnormal thickening of the labrum [15].…”
Section: Discussionmentioning
confidence: 99%
“…We also analysed the cystic changes in the acetabulum owing to OA and herniation pit, which is defined as a cystic lesion underneath the anterior cortex at the antero-superior femoral head-neck junction with clear demarcation and diameter of > 3 mm using radiographs and mCT (coronal view) [9, 10].…”
Section: Methodsmentioning
confidence: 99%